Exome sequencing revealed a novel splice site variant in the ALX1 gene underlying frontonasal dysplasia. Issue 3 (12th July 2016) - Ullah, A.; Kalsoom, U.‐E; Umair, M.; John, P.; Ansar, M.; Basit, S.; Ahmad, W.
Abstract : Frontonasal dysplasia (FND) is a heterogeneous group of disorders characterized by hypertelorism, telecanthus, broad nasal root, wide prominent nasal bridge, short and wide nasal ridge, broad columella and smooth philtrum. To date one X‐linked and three autosomal recessive forms of FND have been reported in different ethnic groups. We sought to identify the gene responsible for FND in a consanguineous Pakistani family segregating the disorder in autosomal recessive pattern. Genome‐wide homozygosity mapping using 250KNsp array revealed five homozygous regions in the selected affected individuals. Exome sequencing found a novel splice acceptor site variant (c.661‐1G>C: NM_006982.2) in ALX1 . Sanger sequencing confirmed the correct segregation of the pathogenic variant in the whole family. Our study concludes that the splice site variant identified in the ALX1 gene causes mild form of FND. Abstract :